2011
DOI: 10.1016/j.jvs.2010.11.047
|View full text |Cite
|
Sign up to set email alerts
|

The impact of superficial femoral artery (SFA) occlusion on the outcome of proximal sartorius muscle transposition flaps in vascular surgery patients

Abstract: Biologic protection procedures as local muscle flaps are vital adjuncts to vascular surgery techniques in the treatment of complicated wounds in the groin. Occlusion of the SFA in the presence of a patent PFA is not associated with an increased risk of flap loss in proximal sartorius muscle rotational flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…When the deep femoral artery is patent, the patency of superficial femoral artery does not affect the viability of the SMF. 241,242 However, SMF viability is compromised when the deep femoral artery is occluded. In such cases, revascularisation of the deep femoral artery is needed, either directly or indirectly (obturator bypass).…”
mentioning
confidence: 99%
“…When the deep femoral artery is patent, the patency of superficial femoral artery does not affect the viability of the SMF. 241,242 However, SMF viability is compromised when the deep femoral artery is occluded. In such cases, revascularisation of the deep femoral artery is needed, either directly or indirectly (obturator bypass).…”
mentioning
confidence: 99%
“…Those who support the notion of a type 4 segmental supply remain cautious using the muscle in circumstances where the superficial femoral vessel is compromised. However, in a study by Töpel et al, 13 a sample group of 53 patients with 56 SM flap transpositions were observed for flap viability, 23 of which had patent superficial femoral arteries and 33 were occluded. The deep femoral artery was classified as patent in all 56 cases.…”
Section: Discussionmentioning
confidence: 98%
“…After an average follow-up time of 6.4 months, 54 viable flaps were documented. Much like Ramasastry et al, 34 Töpel et al 13 proposed that the patency of the superior femoral artery has little to do with flap viability, provided the deep femoral artery remains open and undiseased. In all the 5 of our patients, a viable SM flap could be harvested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood supply to the rectus femoris muscle is also largely from the profunda femoris artery [15]. Ligation of the superficial femoral artery (SFA) may not affect the viability of the sartorius muscle flap, but this possibility may not extend to cases in which both the SFA and the profunda femoris arteries have been ligated [16].…”
Section: Discussionmentioning
confidence: 99%